Pros and Cons of Bogor City Regional Regulation Number 10 of 2021 on Prevention and Countermeasures of Sexual Deviant Behavior in Bogor City - Turobi’ah, Annisa; Rahayu, Susi Dian (UIN Sunan Ampel Surabaya, 2023)
Bogor City is one of the regions in Indonesia that has a high number of HIV AIDS cases in Indonesia. Until 2021, there were 111 cases of HIV AIDS, one of which was caused by sexual deviance. In Bogor City, from 2018-2021 there were 790 cases of sexual deviance. To prevent the practice of sexual deviance from becoming more widespread, the Bogor City Government together with the Bogor City DPRD drafted Regional Regulation No. 10 of 2021 concerning Prevention and Countermeasures of Sexual Deviance in Bogor City (P4S). However, the regulation has drawn pros and cons among the public. The cons considers that this regulation contains elements of human rights violations that exacerbate violence and discrimination against Lesbian, Gay, Bisexual and Transgender groups in Bogor City. Meanwhile, the pro community considers this regulation as an effort to prevent sexual deviations from the Bogor city government. This research uses ROCCIPI theory by Ann Seidman, Robbert B. Seidman and Nalin Abeyserkere by using 7 categories which include Rule, Opportunity, Capacity, Communication, Interest, Process and Ideology. The results of this study are in the preparation of this regulation, most of the mass organizations that reject the regulation are mass organizations outside the city of Bogor, most of which are mass organizations on a national to international scale. While the majority of the people of Bogor city support the P4S regulation, during the process of drafting the regulation there was no rejection from the people of Bogor city.